Pengaruh Motivasi Kerja terhadap Pelaksanaan Program Keselamatan dan Kesehatan Kerja di Unit Pengolahan Heavy Oil Complex (HOC) PT.Pertamina (Persero) Refinery Unit II Dumai Riau Tahun 2013 - Zuhdina Ulva; dr.halinda sari lubis,M.KKK; Isyatun Mardiyah,SKM,M.Kes (Lingkungan dan Kesehatan Kerja, 2014)
Occupational health and safety program is very important for the company, making it PT. Pertamina Refinery Unit II Dumai put the occupational security and  safety in the first rank ( safety first ). Based on the monthly evaluation which done by HSE section the unstable achievement aspects occupational safety especially for HSE Awareness program (Awareness of safety health workers in work environment). One way to provide motivation for the employee allegedly can improve awareness that the importance of employees work safety and health in the work environment. The aim of research is to know the influence of work motivation (intrinsic and extrinsic) on the implementation occupational health and safety program in the Heavy Oil Complex Unit (HOC) PT.Pertamina (Persero) Refinery Unit Dumai II by 2013. This research is survey of analytic with cross sectional design,  sample taken a whole of employees (75 people). Analysis of the data used is univariat, bivariat with Spearman Correlations test. The result of research showed that there was significant correlation between intrinsic and extrinsic work motivation with the implementation of occupational safety and health program, with p value < 0,05. The suggestions for management and heads sections (HOC) PT.Pertamina (Persero) Refinery Unit II Dumai are to increase collaboration so as to maintain the work motivation (intrinsic and extrinsic) in the Heavy Oil Complex Unit (HOC). Keywords:    Motivation, HSE Awareness, HOC (Heavy Oil Complex)